PENERAPAN METODE PEMBELAJARAN QUANTUM LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN MEKANIKA TEKNIK SISWA KELAS X SMK NEGERI 7 BALEENDAH - Saputri, Din Nur Laila (2017)
Penelitian ini dilakukan untuk : (1) Mengetahui bagaimana penerapan pembelajaran Quantum Learning dalam mata pelajaran Mekanika Teknik, (2) Memperoleh besaran peningkatan hasil belajar menggunakan pembelajaran Quantum Learning. Metode penelitian yang dilakukan menggunakan eksperimen dengan populasi siswa kelas X Teknik Gambar Bangunan SMKN 7 Baleendah. Sampel pada penelitian ini adalah siswa X TGB 1 sebagai kelas eksperimen menggunakan pembelajaran Quantum Learning dan X TGB 2 sebagai kelas kontrol menggunakan pembelajaran metode ceramah. Penelitian dilaksanakan pada mata pelajaran Mekanika Teknik. Instrument yang digunakan adalah tes, lembar observsi siswa, dan lembar observasi guru. Desain penelitian yang digunakan adalah Non-equivalen Group Design. Pengolahan data penelitian dilakukan secara analisis dengan pendekatan kuantitatif. Penerapan pembelajaran Quantum Learning dapat terlaksana dengan baik. Dari hasil penelitian menunjukan bahwa terdapat peningkatan hasil belajar siswa setelah mengikuti model pembelajaran Quantum Learning dengan kategori tinggi nilai N-gain = 0,75. Kelas eksperimen memiliki nilai rata-rata 77.64 dengan 17 siswa mencapai kriterian ketuntasan minimal (KKM), dan kelas kontrol memiliki nilai rata-rata 63,64 dengan 10 siswa mencapai kriteria ketuntasan minimal (KKM) dengan nilai N-gain = 0,57. Educator became one of the influence of the most complex because to set an example and a role model for students .The attitudes and behavior educator also be a bust for students at the time provide learning .Educator said to be has not been successful in mastering class if students less enthusiastic in following learning experiences and observations conducted at the pra-penelitian on the subjects of mechanics technique , educator little regard for an effective method in their experiences which is done .It makes learning outcomes students took part in the low .Learning outcomes students low indicated to the fact the following: ( 1 ) the average class x tgb is 51,45 or 91 percent of students are below the value criteria ketuntasan minimal ( kkm ) , while kkm subjects mechanics technique is 75 .( 2 ) there are an acknowledgment of 87.5 percent of students that mechanics technique is one of the subjects difficult .These results show mechanics techniques is the subject that is difficult for students and need an increase in the results. This research was conducted to : (1) find out how was Quantum Learning application on mechanics technique subject, (2) to obtain the amount of increase in learning result using Quantum Learning. This research used experimental design with population was student grade 1 TGB in 7 vocational high school Baleendah. The sample of this research are student TGB 1 as an experimental class used quantum learning and TGB 2 as control class use speech learning. The instrument used in the research are test, observation for teacher, and observation sheet for student. The design of the research is non equivalent group design. From the result of the research indicate that there is an increase of learning outcomes after following the quantum learning, with categories is high. Experimental class has a n-gain = 0.75 with mean 77,64 and student who achieved minimum learning mastery standard are 17 students. Control class has n-gain = 0,57 with 10 students achieved the minimum learning mastery standard. Keyword : minimum learning mastery standard, study result, Quantum Learning,